Touchless classes and absent bodies: Teaching physical education in times of Covid-19 - Varea, V.; González-Calvo, G. (Sport, Education and Society, 2021)
Bodies have been claimed to be an`absent presence`and touch`risky business`in physical education (PE). We have now witnessed how these claims are intensified in pandemic times of Covid-19, particularly incountries that have adopted extreme lockdown measures. This paper explores how PE practices have become`touchless`and bodies absent using the theoretical concepts of risk and assemblage. The paper focusses on a group of pre-service PE teachers who were keen on undertaking their PE practicum experience and who were forced to switch to online mode. Data were collected through participant-produced drawings and comments on the drawings. Results suggest that the pre-service teachers are experiencing a mix of emotions duringthis time, miss the physical contact with students and believe the subject of PE is losing its identity as a consequence of the current situation. The conclusions of this study reveal a shift in the way that bodies are being constituted as assemblages now, and the possibility that pre-service teachers are missing out on an important aspect of their practicum experiences because of the lack of direct contact with students. We also wonder if pre-service teacher education programmes should put more emphasis on better preparing the students to teach online, and what will be the long-term consequences in the teaching of PE because of the current Covid-19 pandemic situation